Perception of village society about management of village finance and its benefits / Ni Putu Setia Devi Astini ... [et al.] - Devi Astini, Ni Putu Setia; Dwi Astuti, Baiq Rosyida; ., Alamsyah (2019)
Data is obtained through survey methods by giving questionnaires to respondents. The research respondents were 105 people from 3 villages in Labuapi District, West Lombok Regency. 40 statements in the questionnaire were built from 7 indicators. The first focus of research, village financial management, consists of 3 indicators, namely planning, implementation and reporting quality. The second, benefits of village financial management, consists of 4 indicators, namely the benefits of village finance in the administration of village government; benefits in the construction of infrastructure and the village environment; benefits in community empowerment; and the impact of village finance. The rating scale is from 0 to 10. Scores are divided into 5 categories: very low, low, medium, high and very high. The score of each respondent was calculated by the maximum value of the research indicator divided by the number of categories.